Sidorenko O., Laguta M. Gender variations of artistic representation of сoncept «Love» in modern prose - Sidorenko O.; Laguta M. (Philological Treatises, 2020)
The article is devoted to studying of the gender peculiarities of language occurrences of associative and semantic structure of concept of «Love» in the author’s linguistic view of the world. The gender factor of artistic representations of concept of «Love» is determined by mental exposition of author as a medium of social sex and is foregrounded with social role of characters. Contextual associative and semantic field is a verbal expression of gender meaning of artistic concept of «Love», content and structure of which shows us, according to lexical and syntactical point of view, gender variations of conceptual meaning of «Love» in Rozdobudko’s and Vynnychuk’s compositions writings don’t have a vivid expression. Authors’ speech is equal according to using expressive means, but gender factor appears in ideologically-thematic view more, than in linguostylistic one. Artistic discourse of both authors composes gender values of a reader: reflects sociocultural stereotypes and at the same time arranges new gender figures – emphasizes intellectual content in woman’s emotions and feelings and ascribes tenderness and devotion for men’s passion.